(3GdGUWaG aj TQM ZQjH GdTaGs - (3eMeO GdOdLj , eMeO Hf eMeO Hf eMeO GdOdLj GdYKeGfj GdTGaYj, TeS GdOjf,J (B947 (3g` s
(3ChdgG (B:s
(3dNUJg ef cJGH GdGcJaG ai HjGf CdaGX GdTaG JCdja GdGeGe JGL GdOjf CHj Gdjef YHO GdHGbi GdjeGfi s
(3BNQgG (B:s
(3hhQO ai MjR GdGeQ GdeLQO Ohf GdNHQ MSf JCcjOg GfJgi JdNjUfG s
(3cJGH GdEcJaGA ai TQM dcJGH GdTaG ai Mbhb GdeUWai ddbGVi YjGVs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B265s
(3eUOQ GbJfGA GdCUd (B:s
(3eQcR GdHMK GdYdei (B- (3Ce GdbQi s
Keywords: (3eJaQbGJs